Stapled hemorrhoidopexy versus Milligan-Morgan haemorrhoidectomy: a paradigm shift in the management of 3rd and 4th degree hemorrhoids - Panigrahi, Sudhir Kumar; Behera, Chinmaya Ranjan; Mishra, Subrajit; Kanungo, Abinash (International Surgery Journal, 2017)
Background: Hemorrhoids being a common anorectal problem with its well known morbidity and complications is treated since long by conservative measures, injection sclerotherapy or rubber banding for 1st and 2nd degree and by open Miligan Morgan hemorrhoidectomy or closed Fergusson hemorrhoidectomy for 3rd and 4th degree. However, since 1998, the adoption of Stapled Hemorrhoidopexy has proved over time to be a better alternative in terms of lesser postoperative complication and an overall patient satisfaction. Methods: A prospective study conducted on 114 patients at Department of General Surgery, Kalinga institute of Medical Sciences, Bhubaneswar, Odisha from May 2014 to December 2016. Results: Our study showed stapled hemorrhoidopexy, significantly reduced the time taken for the operative procedure (p <0.001), post operative pain (p <0.01), hospital stay along with early return to work and a better patient satisfaction. Conclusions: Stapled hemorrhoidopexy is an effective alternative to open Miligan-Morgan procedure in treating 3rd and 4th degree hemorrhoids, in terms of lesser time taken for the operative procedure, post operative pain, use of analgesics, hospital stay and early return to work, better post operative patient’s satisfaction and reduced procedure related complication.